Mechanism of Dun1 Activation by Rad53 Phosphorylation in Saccharomyces cerevisiae - Chen, Sheng-hong (2006)
Despite extensive studies, the molecular mechanism of DNA damage checkpoint activation remains incompletely understood. To better dissect this mechanism, we developed an activity-based assay for Dun1, a downstream DNA damage checkpoint kinase in yeast, using its physiological substrate Sml1. Using this assay, we confirmed the genetic basis of Dun1 activation. Rad53 was found to be directly responsible for Dun1 activation. We reconstituted the activation of Dun1 by Rad53 and found that phosphorylation of Thr-380 in the activation loop of Dun1 by Rad53 is responsible for Dun1 activation. Interestingly, phosphorylation of the evolutionarily conserved Thr-354 in the activation loop of Rad53 is also important for the regulation of Rad53 activity. Thus, this conserved mode of activation loop phosphorylation appears to be a general mechanism for the activation of Chk2 family kinases.